Milk-based culture of Penicillium camemberti and its component oleamide affect cognitive function in healthy elderly Japanese individuals: a multi-arm randomized, double-blind, placebo-controlled study - Sasaki, Mayuki; Oba, Chisato; Nakamura, Kentaro; Takeo, Hiroki; Toya, Hidemasa; Furuichi, Keisuke (Frontiers in Nutrition, 2024)
Dairy products and fermented foods have a reported association with maintained cognitive function. Camembert cheese, a dairy product fermented by the white mold Penicillium camemberti, has also been shown to enhance cognitive function in vivo. Oleamide, derived from the fermentation of the white mold, is a candidate for an active component, and expected to improve both cognitive function and sleep conditions. Thus, this study investigated whether the milk-based culture of white mold (MCW), and oleamide, could improve cognitive function and sleep state clinically. A multi-arm randomized, double-blind, placebo-controlled trial was conducted in Tokyo, Japan. 60 healthy Japanese individuals aged 50-75 who were aware of their cognitive decline were randomly and equally divided into three groups of 20 participants using computer-generated random numbers. Participants took either MCW (equivalent to 60 μg/day of oleamide), 60 μg/day of oleamide, or placebo capsules for 12 weeks. Serum BDNF, cognitive function by Cognitrax as primary and MCI Screen as secondary outcome, and sleep status using the Japanese version of the Pittsburgh Sleep Quality Index (PSQI-J) were assessed before and after intervention. The participants, outcome assessors and analysts, and research assistants were blinded to the group assignment. Of the 60 participants, 58 completed the study and were analyzed. No adverse events related to test foods were observed. The placebo group showed a negative rate of change in serum BDNF (−10.5±19.7%), whereas the MCW and oleamide groups showed positive changes (2.0±27.1% and 1.3±13.5%, respectively). Cognitrax scores increased after 12 weeks in all groups. Conversely, the MPI score of the MCI Screen demonstrated a significant improvement in the MCW and oleamide groups compared to the placebo group (p = 0.013 and p < 0.001, respectively). The subscales, immediate free recall and delayed free recall, also significantly increased in them compared to the placebo group. Although PSQI-J revealed no significant differences among groups, the MCW and oleamide groups showed significant improvement after intervention in overall score, subjective sleep quality, and sleep latency. Our results suggest that MCW and its component, oleamide, are safe and contribute to maintaining cognitive functions, particularly short-term and working memory, and improving sleep state.